PENGARUH KONSUMSI JANTUNG PISANG TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS DI PUSKESMAS DELITUA - Vitrilina - Hutabarat (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Breast milk is the first and foreive food that is best for babies. The thing that needs to be considered by post partum mother giving breast milk to the baby is by consuming fruit and vegetables that can increase the amount of breast milk. Banana heart contains lactogogum which has performance stimulating oxytocin and prolactin hormones such as alkaloids, polyphenols, steroids, flavonoids, which are effective in increasing breast milk production. In this case, researchers conducted nonpharmacological studies such as banana heart consumption. This research aims to find out the effect of Banana Heart Consumption on increased breast milk production in post partum in Delitua Health Center by 2020. The method used is the Quasi Experiment method with the research design of One Group Pretest-Postest. The samples in this study were as many as 20 post partum in Deli Tua health center, using total sampling techniques. Data collection is carried out in the form of observation and questionnaires. The statistical test used is the t test. The results showed that there was an influence increase in breast milk production in post partum mothers after consuming banana blossoms with a value of P-Value of 0,000 <0.05. Based on the results of the study, the increase in breast milk production in the mother occurred because the content found in the heart of bananas is lactogogum which has the performance of stimulating oxytocin hormones and prolactin alkaloids, polyphenols, steroids, and flavonoids in increasing the production of breast milk.